DEVELOPING A STANDARD OF MEASUREMENT FOR USER EXPERIENCE IN E-COMMERCE - Kasan, Eginata
Rapid growth of the e-commerce industry has caused a lot of competition. One of the ways to gain more consumers is by improving user experience (UX) on the platform. A good user experience means high level of satisfaction for the user, increasing the chance to attract new users and gaining loyalty of existing users. There are lots of UX metrices that can be used, but no specific standard of measurement for e-commerce has been created. The focus of this research is to formulate a reliable standard of measurement to score an interaction design that is specific for e-commerce. The method for this research is as follows: analysis on what usability and UX goals are needed for e-commerce, analysis on existing UX metrices, solution formulation, and evaluation. Literature review and analysis shows that there are 4 usability goals (effectiveness, efficiency, safe to use, easy to use/learn) and 4 UX goals (helpful, rewarding, engaging, fun/enjoyable) that needs to be achieved in an e-commerce platform. The proposed standard of measurement in this research is a combined / comparative metric consisting of task success rate, task time, SEQ, UEQ, and NPS. The internal reliability is measured by Cronbach’s Alpha and results shows an acceptable level of reliability (above 0.6) across three e-commerce applications. Pearson Coefficient Alpha of 0.994 shows high correlation between the resulting score and rating of the three apps in Google Play Store.